Unusual Presentation of Vivax Malaria with Anaemia, Thrombocytopenia, Jaundice, Renal Disturbance, and Melena: A Report from Malang, a Nonendemic Area in Indonesia. (29th December 2013) - Fitri, Loeki Enggar; Sardjono, Teguh Wahju; Hermansyah, Bagus; Candradikusuma, Didi; Berens-Riha, Nicole
Abstract : Most of the complications of malaria such as anaemia, thrombocytopenia, jaundice, and renal failure are commonly found in Plasmodium falciparum malaria, but the incidence of severe and complicated vivax malaria tends to be increasing. We report two cases of severe Plasmodium vivax malaria from Malang, a nonendemic area in Indonesia. Patients exhibited anaemia, thrombocytopenia, jaundice, renal disturbance, and melena. Microscopic peripheral blood examination and amplification of parasite 18s rRNA by polymerase chain reaction showed the presence of P. vivax and absence of P. falciparum . All patients responded well to antimalarial drugs.